Critical Care Medicine in Bangladesh: Evolution and Challenges - Faruque, Mohammad Omar (Journal of Chittagong Medical College Teachers’ Association, 2011)
DOI: 10.3329/jcmcta.v21i1.7661 Journal of Chittagong Medical College Teachers' Association 2010: 21(1):3-5